Scholars in health equity: a program of structured physician faculty development - Ring, Jeffrey; Torres, Daisy; Ramos, Rosio; Gonzalez, Cristina M.; Nahid, Musarrat; Morales, Susana; Phillips, Erica (Journal of General Internal Medicine, 2024)
Structured faculty development programs focused on integrating health equity into medical education curricula remain limited.
Keywords: adult learning theory; anti-racist curricula; dept.dei; faculty development; health equity; medical education; peer-reviewed

Educational redlining: Bridging historical contexts to contemporary practice - Rutledge, K.E; Robinson-Morris, D.W. (Resisting Divide-and-Conquer Strategies in Education: Pathways and Possibilities, 2024)
Resisting Divide-and-Conquer Strategies in Education: Pathways and Possibilities examines the ways in which divide-and-conquer strategies operate in the American public education system. In U.S. education, these mechanisms are endemic and enduring, if not always evident. Coordinated, strategic, well-funded, politically-viable campaigns continue to stoke fear, othering, villainization, and dehumanization of minoritized groups, pushing false and problematic narratives that inhibit progress toward social justice. Weaponizing hegemony and leveraging misinformation, reactionary agents and institutions seek to suppress truth, block access to democratic participation, and dismantle education and other sites of emancipatory possibility through the strength of divide-and-conquer mechanisms, pitting relatively disempowered groups against one another to preserve the dominant social order. Readers of this book will encounter conceptual and critical interrogations of divide and conquer. The text will help facilitate inquiry and engagement into how divide and conquer operates and how it can be resisted. It looks at the history of the phenomenon, as well as its current state, especially as it relates to education. What insights and lessons might we learn from a focused examination of divide and conquer, and what strategies of resistance are both possible and necessary for challenging it? This text is designed for undergraduate and graduate classrooms in education and social sciences. Part I, Ideology and Sociopolitical Contexts, dissects how divide-and-conquer mechanisms operate ideologically and sociopolitically. Part II, Policies and Practices, focuses on how divide-and-conquer mechanisms shape exclusionary U.S. educational policies and practices. Part III, Resistance and Liberation, documents efforts of liberatory communicative, curricular, and pedagogical possibilities. Each chapter concludes with a set of critical questions for reflection and engagement.Perfect for courses such as: Foundations of Education; Schools and Society; Schooling in America; History of Education; Philosophy of Education; Sociology of Education; Social Studies; Critical Theory in Education
Keywords: dept.dei

A chief diversity officer's perspective: Advocacy and allyship-how can I help? - Ariza, D. (How to Incorporate Equity and Justice in Your Teaching, 2024)
Keywords: dept.dei